IMPROVING THE STUDENTSâ READING COMPREHENSION USING TIERED TASKS STRATEGY - Natsir, Ratu Yulianti; Asrawiah, Asrawiah (Lembaga Perpustakaan Unismuh Makassar, 2013)
This research aimed to explain the studentsâ achievement in literal reading comprehension using Tiered Tasks Strategy, as well as to explain the studentsâ achievement in interpretative reading comprehension using Tiered Tasks Strategy. This research used Classroom Action Research and applied to cycles in application, they are cycle 1 and 2 with 4 meetings in every cycle. The improvement of studentsâ ability to write narrative text using Tiered Tasks Strategy had effective effect. The researcher found that before the application of tiered tasks strategy the studentsâ score is 52.53(fair) but after using the method the studentsâ score in cycle I is 62.14 and in the cycle II become 77.18. So, the improvement of the studentsâ score of d-test to cycle I is 18.93% whereas the development of the studentsâ ability of d-test to cycle II is 47.80% and the improvement from cycle I to cycle II is 24.22%.Keywords: Reading, Tiered, StrategyPenelitian ini bertujuan untuk menjelaskan prestasi dalam pemahaman siswa dalam membaca literal menggunakan Strategi Tugas berjenjang, serta menjelaskan prestasi siswa dalam pemahaman membaca interpretatif menggunakan berjenjang Tugas Strategi. Penelitian ini menggunakan Penelitian Tindakan Kelas dan diterapkan untuk siklus dalam aplikasi, diantaranya adalah siklus 1 dan 2 dengan 4 pertemuan pada setiap siklus. Peningkatan kemampuan siswa untuk menulis teks naratif menggunakan Strategi Tugas berjenjang memiliki efek yang efektif. Peneliti menemukan bahwa sebelum penerapan strategi tugas berjenjang siswa skor adalah 52, 53 (cukup) tapi setelah menggunakan metode skor siswa pada siklus I adalah 62, 14 dan pada siklus II menjadi 77, 18. Jadi, peningkatan skor d-tes siswa untuk siklus I adalah 18, 93% sedangkan perkembangan kemampuan siswa pada d-test ke siklus II adalah 47, 80% dan peningkatan dari siklus I ke siklus II adalah 24, 22%.Kata Kunci: Reading, berjenjang, Strategi.